Automatic design of the flexural strengthening of reinforced concrete beams using fiber reinforced polymers (FRP) - doi: 10.4025/actascitechnol.v34i2.8318 - Souza, Rafael Alves de; Ferrari, Vladimir José (Acta Scientiarum. Technology, 2011)
Changing the functions of a building, the presence of some design or construction errors, the incidence of seismic actions and even the updating of design codes may demand the strengthening of certain structures. In the specific case of reinforced concrete structures it is desirable the application of a technique of strengthening which is fast, economic and efficient, in order to provide advantages when an intervention is necessary. The technique of strengthening chosen must provide less disorder as possible as well as the guaranty of safety. Taking into account this scenery, fiber reinforced polymers have been working as a very attractive alternative for rehabilitating in-service structures. In that way, the present study aims at presenting the main properties of this new material as well as the design routines for flexural strengthening of reinforced concrete beams. Finally, a package-software developed into the MATLAB platform is presented, intending to generate a simple tool for the automatic design using fiber reinforced polymers.